Modulation of Immune Response by Organophosphorus Pesticides: Fishes as a Potential Model in Immunotoxicology - K. J. G. Díaz-Resendiz; G. A. Toledo-Ibarra; M. I. Girón-Pérez (Journal of Immunology Research)
Immune response is modulated by different substances that are present in the environment. Nevertheless, some of these may cause an immunotoxic effect. In this paper, the effect of organophosphorus pesticides (frequent substances spilled in aquatic ecosystems) on the immune system of fishes and in immunotoxicology is reviewed. Furthermore, some cellular and molecular mechanisms that might be involved in immunoregulation mechanisms of organophosphorus pesticides are discussed.